Manifestation of Social Identifications of Would-be Physical Education and Sports Specialists (Baltic Journal of Sport and Health Sciences, 2018)
Research deals with the problem what social identifications are characteristic of the higher school students and howthey are related to other factors influencing them. Research object was the social identifications of students. Researchaim was to characterize the manifestation of social identifications of would-be physical education and sportsspecialists and to reveal their links with the independent variables of the research. Research participants were 6221—4 th  year students of the Lithuanian Academy of Physical Education, the faculties of Sports Education and SportsTechnologies. The social identifications of students were measured using M. Hooper (1976) Social IdentificationMeasurement Scale. The factor analysis of social identifications distinguished five factors. Social identificationstypical of would-be specialists of physical education and sports were linked to social prestige (wish to have a well-paid job and be respected in the society), family (the roles of husband / wife, father / mother), age (importance of beingadult), nationality (importance of being Lithuanian) and political activity (wish to belong to or support a politicalparty). The distinguished social identifications were related to gender (girls compared to boys want more to be adults,but their national identification is weaker), academic achievements (higher achieving students are more identifiedwith family, and it is more important for them to be adults), sports activities (students higher achieving in sports aremore identified with their nationality) and other sociodemographic indicators (better-off students want to be adultsmore, and national identification is more important to those students whose parents are blue-collar workers andfarmers compared to the children of white-collar workers).Keywords: social identifications, higher education, Social Identification Measurement Scale.